PENGARUH ATTITUDE TOWARD THE ACTOR, MOVIE, CHARACTER TERHADAP ATTITUDE TOWARD PRODUCT PLACEMENT DAN BRAND PADA DRAMA KOREA GOBLIN DI INDONESIA - Khaulah Al-Khansaa; Indarini Indarini; Silvia Margaretha (CALYPTRA, 2018)
The purpose of this study is to investigate the impact of attitude toward the product placement on attitude toward the brand with several attitudinal constructs (attitude toward the actor, character, movie) that influence attitude toward the product placement in Korean drama ‘Goblin’. Method analysis that use in this study is structural equation modeling (SEM). The object of this study is Indonesian viewer who use an internet forum for Korean drama fans, who also watch Korean drama ‘Goblin’ and could recall at least one product placement in the drama. There are 200 respondents that participate in the study. Data processing using SPSS 22 software for Mac OS and Lisrel 32 for Windows OS. The result of this study indicated that attitude toward product placement has significant positive effect on attitude toward the brand, but the attitudinal constructs like actor, movie and character did not have any effect on product placement. The fit between actor and brand have a significant effect on product placement.